Diagnosis and Treatment in patient with Herlyn-Werner-Wunderlich Syndrome: A case causing pelvic pain - Norman Aji Triantoro; Nuring Pangastuti (JURNAL KESEHATAN REPRODUKSI, 2021)
ABSTRACTBackground: Herlyn-Werner-Wunderlich (HWW) syndrome is a rare variant of Mullerian duct anomalies. The characteristic triad of this syndrome includes didelphys uterus, obstructed hemivagina, and ipsilateral renal agenesis, recently known as Obstructed Hemivagina and Ipsilateral Renal Anomaly (OHVIRA) syndrome. The most common presentation is abdominal and pelvic pain, dysmenorrhea, and abdominal mass secondary to hematocolpos, hematosalping or hematometra.Objective: to determine the diagnosis and operative management of HWW syndrome case with pelvic pain as the chief complaint.Methods: case examination and tracing medical records at Dr Sardjito Hospital Yogyakarta.Results and Discussion: Fourteen-year-old female, presented with pelvic pain. Physical examination revealed a cystic mass in the abdomen inferior, palpable up to 3 cm inferior to the umbilicus. From the Intravenous Pyelography (IVP) examination, it was found normal anatomy and function of the right kidney, but there was no left kidney. On a contrast-enhanced abdominal CT scan, magnetic resonance imaging (MRI) and laparoscopy showing a complete duplication of the uterus from the horn to the cervix with no connection between the two uterine cavities, both ovaries were normal, the right fallopian tube was normal, the left tube was enlarged, attached to the uterus and the left ovary, no left kidney was found. Operative management of the vaginal septectomy procedure was performed.Conclusion: MRI is most accurate for providing details regarding the altered anatomy and for identifying associated hematocolpos,hematosalping or hematometra for HWW syndrome cases. Surgical intervention by vaginal septectomy is performed to relieve symptoms, provide better reproductive and sexual functions.Keywords: Herlyn-Werner-Wunderlich syndrome, Mullerian disgenesis, pelvic pain. ABSTRAKLatar belakang: sindrom Herlyn-Werner-Wunderlich (HWW) adalah varian langka dari kelainan duktus Mullerian. Trias khas dari sindrom ini adalah uterus didelfis, septum hemivagina, dan agenesis ginjal ipsilateral atau sindromObstructed Hemivagina and Ipsilateral Renal Agenesis (OHVIRA). Gejala paling sering adalah nyeri perut maupun panggul, dismenorea, dan terdapatnya massa pada perut akibat dari hematokolpos, hematosalping atau hematometra.Tujuan: untuk mengetahui penegakan diagnosis dan penatalaksanaan operatif satu kasus sindrom HWW dengan keluhan utama nyeri panggul.Metode: pemeriksaan kasus dan penelusuran rekam medis di RSUP Dr Sardjito Yogyakarta.Hasil dan Diskusi: Perempuan berusia 14 tahun dengan nyeri panggul. Pemeriksaan fisik terdapat massa kistik di perut bagian inferior, teraba hingga 3 cm inferior umbilikus. Dari pemeriksaan Intravenous Pyelografi (IVP) didapatkan anatomi dan fungsi ginjal kanan yang normal namun tidak didapatkan adanya ginjal kiri. Pada CT scan abdomen dengan kontras, Magnetic Resonance Imaging (MRI) dan laparoskopi menunjukkan duplikasi lengkap uterus dari cornu ke serviks tanpa hubungan antara dua rongga uterus, kedua ovarium normal, tuba fallopi kanan normal, tuba kiri membesar, menempel pada uterus dan ovarium kiri. tidak didapatkan ginjal kiri. Selanjutnya dilakukan penatalaksanaan operatif prosedur septektomi vagina.Kesimpulan: MRI paling akurat untuk memberikan rincian mengenai perubahan anatomi dan untuk mengidentifikasi hematocolpos, hematosalping maupun hematometra pada sindrom HWW. Intervensi bedah berupa septektomi vagina dilakukan untuk meredakan gejala serta memberikan harapan fungsi reproduksi dan sexual yang lebih baik.Kata kunci: Sindrom Herlyn-Werner-Wunderlich, disgenesis Mullerian, nyeri panggul.